A systematic approach towards a zero-waste water treatment: clay-carbon composite adsorbents made from drinking water treatment sludge - Lucas Landwehrkamp; Minja Bogunović Koljaja; Munima Sultana; Ivana Ivančev-Tumbas; Stefan Panglisch (npj Clean Water)
Abstract Increasingly stringent water quality standards are forcing more water treatment facilities to implement adsorption steps. Activated carbon is efficient but has a high environmental impact due to CO₂ emissions and energy demand. Adsorbents derived from water treatment residuals offer a potential solution. In this study, a novel laboratory rotary furnace was designed to produce clay-carbon composite adsorbents from drinking water treatment residues. The process was optimized using a statistical design of experiments, representing the first comprehensive statistical analysis of the thermal activation of such residuals. Thermal activation increased the specific surface area almost tenfold (112–201 m²/g). The adsorbents were tested for removal of ibuprofen, caffeine, diclofenac (1 µg/L), and brilliant blue FCF (5 mg/L). Response surface models showed that heating rate (p < 0.003) and ramp duration (p < 0.00002) significantly influenced adsorption capacity. Mass balance calculations suggest on-site production could fully substitute activated carbon and generate surplus material.